Geographical barriers and serological relationships in some african toads of the Bufo regularis complex - Cei, José Miguel Alfredo María (1973)
Serological relationships of several African toads of the Bufo regularis group have been studied. Two fundamental assemblies of populations were recognizable by crossed precipitin tests. They seem correpond to the Blair’s «Western» and «Eastern» groups in accordance with their reciprocal rate of genetic compatibility. Between the regularis toads North and South of Cunene river percent values of homo-heterologous precipitin reactions range between 70.4 - 72.9 %. On the other hand the Angolan populations and the isolated regularis populations from Djanet (Sahara: Algeria) show values ranging between 80.6 - 87.0 %, in spite of the wide geographical intervals. Serological distance increases between regularis toads and the several allo- -sympatric species belonging to the same regularis complex, such as pardalis, rangeri or maculatus-pusillus, (range of percent values between 60.5 - 69.0%). Furthermore a noticeable similarity is remarkable between rangeri and pardalis (83.7 - 84.7 %) in accordance with Poynton’s systematic statements (1964). Evolutive features of this troublesome group of toads were briefly discussed. The paleogeographic interest of the pleistocenic climatic cycles of the present Saharian Desert and the ancient Kalahari Basin were also emphasized as very important ecological barriers.